2020
DOI: 10.1016/j.jmig.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combined Bipolar Radiofrequency Impedance-Controlled Endometrial Ablation with Levonorgestrel Intrauterine System versus Bipolar Radiofrequency Endometrial Ablation Alone in Women with Abnormal Uterine Bleeding

Abstract: This study aims to evaluate the efficacy of the combination of bipolar radiofrequency impedance-controlled endometrial ablation (NovaSure; Hologic Inc., Bedford, MA) and levonorgestrel intrauterine system (LNG-IUS; Mirena; Schering AG, Berlin, Germany) placement in comparison with NovaSure endometrial ablation alone in patients with abnormal uterine bleeding (AUB). Design: A propensity score matching study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Four retrospective studies with control groups described a hysterectomy rate in the combined treatment group varying between 0% and 11%, whereas treatment with EA alone showed hysterectomy rates varying from 9.4% to 24%. 8,12,14,15 The four studies examining hysteroscopic endometrial resection plus LNG-IUS showed hysterectomy rates of 0%-11%. [12][13][14]17 The remaining four studies investigating non-hysteroscopic EA + LNG-IUS showed 0%-1% hysterectomy rates.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four retrospective studies with control groups described a hysterectomy rate in the combined treatment group varying between 0% and 11%, whereas treatment with EA alone showed hysterectomy rates varying from 9.4% to 24%. 8,12,14,15 The four studies examining hysteroscopic endometrial resection plus LNG-IUS showed hysterectomy rates of 0%-11%. [12][13][14]17 The remaining four studies investigating non-hysteroscopic EA + LNG-IUS showed 0%-1% hysterectomy rates.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
“…[12][13][14]17 The remaining four studies investigating non-hysteroscopic EA + LNG-IUS showed 0%-1% hysterectomy rates. 8,15,16 In two retrospective studies without a control group, a total of two out of 123 women required a hysterectomy after treatment with EA/resection and LNG-IUS, because of ongoing vaginal bleeding. 13,16 In the case series of Bratschi three out of 99 women (3%) required a hysterectomy after the combined treatment, all as the result of (precursors of) cancer.…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations